Assessing the trophic ecology of top predators across a recolonisation frontier using DNA metabarcoding of diets - Hardy, N.; Berry, T.; Kelaher, B.; Goldsworthy, S.; Bunce, Michael; Coleman, M.; Gillanders, B.; Connell, S.; Blewitt, M.; Figueira, W. (Inter-Research, 2017)
Top predator populations, once intensively hunted, are rebounding in size and geographic distribution. The cessation of sealing along coastal Australia and subsequent recovery of Australian Arctocephalus pusillus doriferus and long-nosed A. forsteri fur seals represents a unique opportunity to investigate trophic linkages at a frontier of predator recolonisation. We characterised the diets of both species across 2 locations of recolonisation, one site an established breeding colony, and the other, a new but permanent haul-out site. Using DNA metabarcoding, high taxonomic resolution data on diets was used to inform ecological trait-based analyses across time and location. Australian and long-nosed fur seals consumed 76 and 73 prey taxa, respectively, a prey diversity greater than previously reported. We found unexpected overlap of prey functional traits in the diets of both seal species at the haul-out site, where we observed strong trophic linkages with coastal ecosystems due to the prevalence of benthic, demersal and reef-associated prey. The diets of both seal species at the breeding colony were consistent with foraging patterns observed in the centre of their geographic range regarding diet partitioning between predator species and seasonal trends typically observed. The unexpected differences between sites in this region and the convergence of both predators’ effective ecological roles at the range-edge haul-out site correlate with known differences in seal population densities and demographics at these and other newly recolonised locations. This study provides a baseline for the diets and trophic interactions for recovering fur seal populations and from which to understand the evolving ecology of predator recolonisation.